A Comparison of Calculated with Direct Measurement of Low Density Lipoprotein Cholesterol Level (Journal of Chittagong Medical College Teachers' Association, 2010)
DOI: 10.3329/jcmcta.v20i2.5621Journal of Chittagong Medical College Teachers' Association 2009: 20(2):19-23